Improvement of Workshop Entrance Infrastructure for the Mechanical Engineering Department - Tumengkol, Herman; Kabo, Don (PT FORMOSA CENDEKIA GLOBAL, 2024)
Improvement of Workshop Entrance Infrastructure for the Mechanical Engineering Department of Politeknik Negeri Manado aim is to address the issue of open ground surfaces that serve as pedestrian pathways leading to the Mechanical Engineering practice rooms. During rainy conditions, these pathways become flooded and muddy. The chosen solution is the installation of paving blocks to elevate the pedestrian level. The implementation process includes location identification, design planning, procurement of materials and equipment, installation, monitoring, and evaluation. The expected outcome is a better and more sustainable pedestrian infrastructure, with a positive impact on the campus community through improved infrastructure as part of community service activities